Pijat Laktasi untuk Memperlancar Produksi Asi pada Ibu Nifas Hari Ke Satu Sampai Hari ke Enam - Jesica Permatasari; Septi Tri Aksari; Norif Didik Nur Imanah; Dahlia Arief Rantauni (STIKes Ibnu Sina Ajibarang, 2025)
The postpartum period is a transitional period characterized by physiological and psychological changes. A common problem is disruption of the breastfeeding process, particularly the production of breast milk. Non-pharmacological efforts such as lactation massage can help increase breast milk production. This study aims to determine the effectiveness of lactation massage on the smooth production of breast milk in postpartum mothers using a qualitative case study method, with data obtained through interviews, examinations, and observations. The intervention carried out on Mrs. A was a lactation massage for 15–20 minutes, twice by the researcher and 10 times by her husband with a recommended frequency of massage twice a day in the morning and evening focusing on the breast area. Providing lactation massage to Mrs. A resulted in a significant increase in breast milk production, from 1 ml on the first day to 70 ml on the sixth day. Therefore, lactation massage is effective in increasing breast milk production and can be a supporting method in overcoming breastfeeding obstacles in postpartum mothers.